Lemon Fiber as a New Source of Fat Replacement in Filling Creams - Ozmen, Duygu; Toker, Omer Said; Ozturk, Saniye Akyil (WILEY, 2025)
Developing new sustainable alternatives to fat in food products that maintain textural and rheological properties while offering substantial nutritional value presents a huge challenge in the food industry. Lemon fiber, which is dietary fiber and a by-product of the citrus industry is recognized to have considerable health advantages, due to containing fiber and bioactive substances while having strong rheological characteristics. Present study is composed of two parts. In the first part, usage possibilities of lemon fiber as a fat replacement and optimization were carried out using response surface methodology where the concentration of fat and fiber varied between 10%-25% and 0.5%-1.5%, respectively. The a(w) and pH values of the samples showed a decrease with an increase in lemon fiber considerably (p < 0.05). The sample with fiber to fat ratio of 1.5:25 exhibited the greatest hardness and work of shear values, followed by the control sample, which was recorded as 200.4 +/- 16.75 g and 178.9 +/- 13.10 g s, respectively. Subsequent to this encouraging outcome, 2%, 2.5%, and 3% lemon fiber was used in the sample containing 10% fat. The rheological properties of the samples were markedly enhanced with increased fiber content, while the 3:10 sample (fiber:fat) exhibited no significant change compared to the control sample. The results of the study showed that lemon fiber can be used in filling creams and similar products for fat reduction.
Keywords: fat replacement; filling cream; lemon fiber; rheology; texture; SENSORY PROPERTIES; RHEOLOGICAL CHARACTERISTICS; ORANGE FIBER; OPTIMIZATION; QUALITY; Engineering; Food Science & Technology